Taxonomic review of the genus Commatarcha Meyrick (Lepidoptera: Carposinoidea: Carposinidae) from China, with descriptions of four new species - Qian, Shuonan; Li, Houhun (Zootaxa, 2018)
Nine species of the genus Commatarcha Meyrick, 1935 from China are reviewed. Four species: Commatarcha convoluta Li, sp. nov., C. setiferaedeaga Li, sp. nov., C. hamata Li, sp. nov. and C. rotundivalva Li, sp. nov. are described as new. Commatarcha palaeosema Meyrick, 1935 is newly recorded in China. The male of C. angustiptera Li, 2004 and the female of C. guangxiensis Li, 2004 are reported for the first time. A key to the Commatarcha species in China is given.